Investigating the Factors Affecting Consumer Purchase Intention towards Halal Organic Food - Kamalul Ariffin, Shaizatulaqma; Dihanan, Nur Najihah; Abdul Wahid, Nabsiah (Journal of Entrepreneurship, Business and Economics, 2019)
Organic food industry is currently one of the emerging markets around the world. People begin to realize the advantages of using organic instead of conventional food. Despite taking care of the environment, people are also concerned about their healthy lifestyle. The rising of Muslim consumers in the world has also attracts this industry to react in order to meet Muslims needs and preferences. Organic foods must have a Halal certification to please and win Muslim consumers. The purpose of this paper is to investigate factors, namely, attitudes, subjective norms, perceived behaviour control and price that influence Muslim consumer’s purchase intention towards Halal organic food. To do this, questionnaires were distributed to 208 respondents that shop at organic stores in Penang, Malaysia during end of January until early February, 2019. The relationships between factors were investigated, this study using structural equation modelling (SEM) with partial least square (PLS) version 2.0. The study found that attitudes, perceived behaviour control and price have significant effects on consumers’ purchase intention of Halal organic food, while subjective norms was found to be insignificant. This study contributes to the body of literature by adding price as one of the independent variables to the Theory of Planned Behavior. This study also contributes valuable information to the food and beverage industry indicating that Muslim consumers’ are now looking at Halal logo and certification in order to buy organic food products.   Research paper Keywords: Purchase Intention, Attitude, Perceived Behaviour Control, Subjective Norms, Price Reference to this paper should be made as follows: Kamalul Ariffin, S., Dihanan, N. N., & Abdul Wahid, N. (2019). Investigating the Factors Affecting Consumer Purchase Intention towards Halal Organic Food, Journal of Entrepreneurship, Business and Economics , 7 (2), 162–188.